Uterosacral Nerve Stimulation via Cuff Electrode: A Preliminary Animal Study for Potential Application to Treatment of Preterm Labor - Yi, Jae Lee; Kyu Shik Eom; Hee Youn Kim; Ki Hoon Ahn; Lee, Soo Hyun (2018 40th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC), 2018)
Preterm labor occurs in about 12% of all pregnancies, accounting for at least 75% of neonatal deaths. The neonatal outcomes depend on mainly the gestational age at delivery. The lower the gestational age, the higher the risk of morbidity and mortality. The management of preterm labor involves early detection of high-risk women, prevention and treatment. In this study, the feasibility and stability of implantable cuff electrodes detection and inhibition of uterine contractions for preterm labor treatment were investigated by in-vivo mouse test. In order to check functionality of implanted electrodes, acute in-vivo test at mouse uterosacral ligament was performed by using cuff electrode which stimulate and record nerve activity. As results, the electrical stimulation via a stimulating cuff electrode at mouse uterosacral ligament was properly applied and nerve fiber's signal was recorded via the recording electrode. In addition, the implanted cuff electrodes could obtain stable recording signal to the periodic electrical stimulation for 7 weeks.